Do immigrants pay a price when marrying natives? Lessons from the US time use survey - Shoshana Grossbard-Shechtman; Victoria Vernon (IZA Journal of Development and Migration, 2020)
We compare the allocation of time of native men and women married to immigrants against their counterparts in all-native couples using the American Time Use Survey for the years 2003-18. We find that when intermarried to a native man, immigrant women pay an assimilation price to the extent that, compared to native women in all-native marriages, they work longer hours at paid work, household chores, or both, while their husbands do no extra work. In some cases, they work for just an extra hour per day. Immigrant men do not pay such a price. Some work 34 min less at household chores than native men in all-native marriages, while the native women who marry immigrant men seem to pay a price related to their situation that would be in an all-native marriage. An explanation based on the operation of competitive marriage markets works for immigrant women, but not for immigrant men. Traditionally, gender-based privileges may allow immigrant men to prevent native women from getting a price for the value that intermarriage generates for their husbands. Such a "male dominance" scenario also helps explain why immigrant men married to native daughters of immigrants from the same region get more benefits from intermarriage than other immigrants.
Keywords: D13; J12; J22; 330; time use; immigration; intermarriage; marriage market; gender